2012
DOI: 10.1007/s00424-012-1107-x
|View full text |Cite
|
Sign up to set email alerts
|

The influence of extracellular and intracellular calcium on the secretion of renin

Abstract: Changes in plasma, extracellular and intracellular calcium can affect renin secretion from the renal juxtaglomerular (JG) cells. Elevated intracellular calcium directly inhibits renin release from JG cells by decreasing the dominant second messenger intracellular cyclic adenosine monophosphate (cAMP) via actions on calcium-inhibitable adenylyl cyclases and calcium-activated phosphodiesterases. Increased extracellular calcium also directly inhibits renin release by stimulating the calcium-sensing receptor (CaSR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
39
0
4

Year Published

2013
2013
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(45 citation statements)
references
References 115 publications
(190 reference statements)
2
39
0
4
Order By: Relevance
“…In accordance with those studies, we found that the ultrastructure of those ectopic renin-expressing cells was similar to those of typical juxtaglomerular cells, which are characterized by numerous electron-dense renin storage vesicles (8). In juxtaglomerular cells, renin is released from these vesicles by compound exocytosis (27) triggered by the cAMP signaling pathway (5,14), which is further enhanced by lowering of the extracellular concentration of Ca 2ϩ (1,14,19). Renin secretion from AS Ϫ/Ϫ and WT kidneys was dose dependently stimulated by isoproterenol, which activates the cAMP pathway in juxtaglomerular cells by binding to ␤ 1 -adrenergic receptors (8).…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…In accordance with those studies, we found that the ultrastructure of those ectopic renin-expressing cells was similar to those of typical juxtaglomerular cells, which are characterized by numerous electron-dense renin storage vesicles (8). In juxtaglomerular cells, renin is released from these vesicles by compound exocytosis (27) triggered by the cAMP signaling pathway (5,14), which is further enhanced by lowering of the extracellular concentration of Ca 2ϩ (1,14,19). Renin secretion from AS Ϫ/Ϫ and WT kidneys was dose dependently stimulated by isoproterenol, which activates the cAMP pathway in juxtaglomerular cells by binding to ␤ 1 -adrenergic receptors (8).…”
Section: Discussionsupporting
confidence: 87%
“…It is physiologically mainly regulated via ␤ 1 -adrenergic and ANG II type 1 (AT 1 ) receptors and by the perfusion pressure in preglomerular arterioles (5,14), thus managing a controlled activity of the renin-angiotensin-aldosterone system (RAAS) in the sense of a negative feedback. Renin secretion from cells displays a peculiarity in the way that decreasing the availability of Ca 2ϩ enhances rather than impedes secretion (1,19). In addition, a yet unexplained function of the gap junction protein connexin (Cx)40 is essential for the proper control of renin secretion from juxtaglomerular cells (13,32).…”
mentioning
confidence: 99%
“…Furthermore, calcium has been identified as a regulator of the RAAS at the level of renin [18]. As shown in Figure 1C, calcium acutely inhibits juxtaglomerular cell release of renin via the calcium-sensing receptor (CaSR) [61*], whereas chronic hypercalcemia [62] and chronic stimulation of the CaSR [63] appear to increase plasma renin activity.…”
Section: Calcium- Pth- and Vitamin D-mediated Control Of The Raasmentioning
confidence: 99%
“…Arrows C-F show Ca-, PTH-, and Vitamin D-mediated control of the RAAS. (C) Ca acutely inhibits renin release, but chronic elevations in Ca may stimulate renin production [18]. (D) PTH augments the aldosterone response to AngII [19], and PTH receptors are expressed in aldosterone-producing cells [20].…”
Section: Figurementioning
confidence: 99%
“…It is not surprising, therefore, that a dependent relationship must exist between calcium homeostasis and the RAAS. Perhaps the most widely and detailed descriptions are the interactions of calcium and renin secretion by the juxtaglomerular and renal arteriolar cells(27-31). In contrast to almost all other interactions involving calcium-mediated signaling, in the case of renin release increasing calcium concentrations has an inhibitory effect.…”
Section: Introductionmentioning
confidence: 99%